Modeling the Impact of Geomagnetically Induced Currents on Electrified Railway Signaling Systems in the United Kingdom. Issue 3 (16th March 2023) - Patterson, C. J.; Wild, J. A.; Boteler, D. H.
Abstract: Studies of space weather impacts on ground‐based infrastructure have been largely focused on power networks and pipelines, but railway signaling systems are also affected, with misoperations observed in several countries. This paper advances recent theoretical work on geomagnetically induced currents in railway signaling systems by modeling realistic railway lines with parameters from current industrial standards. Focusing on two example lines in the United Kingdom with different locations and orientation, a range of uniform electric fields are simulated along each modeled line. The results show that misoperations could be caused by geomagnetic interference at disturbance levels expected to recur over timescales of several decades. We also demonstrate that the UK estimate for the geoelectric field induced by a 1 in 100‐year extreme storm would be strong enough to cause widespread signal misoperations in both lines studied. Plain Language Summary: Naturally occurring geomagnetic disturbances caused by space weather can interfere with technological infrastructure in space and on Earth. Previous measurements show that railways in several countries have been impacted, with geomagnetic interference in signaling systems causing wrong signals to be shown. Signaling misoperations can occur when currents that are induced in the rails by space weather interfere with the preset currents from railway infrastructure used to detect trains. This study demonstrates a model that analyses the impacts of geomagnetic activity on two railway lines in the United Kingdom with different orientation and location. The results show that the signaling systems on both lines are susceptible to misoperations caused by geomagnetic interference with a recurrence timescale of several decades. The UK estimates for a 1 in 100 years extreme storm were strong enough to cause a large number of signal misoperations in both lines. Key Points: A model has been set up to examine geomagnetic effects on DC signaling systems on AC‐electrified railways Signal misoperations occurred in both modeled UK railway lines when electric fields expected to arise once every 30 years were applied Extreme 1 in 100‐year geoelectric fields would cause a large number of signal misoperations in both UK railway lines studied